Porphyromonas gingivalis: Major Periodontopathic Pathogen Overview - Jaroslav Mysak; Stepan Podzimek; Pavla Sommerova; Yelena Lyuya-Mi; Jirina Bartova; Tatjana Janatova; Jarmila Prochazkova; Jana Duskova (Journal of Immunology Research)
Porphyromonas gingivalis is a Gram-negative oral anaerobe that is involved in the pathogenesis of periodontitis and is a member of more than 500 bacterial species that live in the oral cavity. This anaerobic bacterium is a natural member of the oral microbiome, yet it can become highly destructive (termed pathobiont) and proliferate to high cell numbers in periodontal lesions: this is attributed to its arsenal of specialized virulence factors. The purpose of this review is to provide an overview of one of the main periodontal pathogens—Porphyromonas gingivalis. This bacterium, along with Treponema denticola and Tannerella forsythia, constitute the “red complex,” a prototype polybacterial pathogenic consortium in periodontitis. This review outlines Porphyromonas gingivalis structure, its metabolism, its ability to colonize the epithelial cells, and its influence upon the host immunity.